Efforts to Improve Student Learning Outcomes through the Think Pair Share Type Cooperative Learning Model on the Theme of Clean Air for Health in Class V of SD Negeri 101948 Bingkat - Audry Zachrah Jannatillah; Dinda Yarshal (Badan Penerbit STIEPARI Press, 2025)
This study aims to decide the application of the think pair share type cooperative learning model on the theme of clean air for health in grade V elementary school students. This study is a classroom action study with the Kemmis and McTaggart model with descriptive analysis. This research was conducted in grade V of SD Negeri 101948 Bingkat, Pegajahan District, Serdang Bedagai Regency. The participants in this study were grade V teachers and grade V students of SD Negeri 101948 Bingkat totaling 31 students. The data collection techniques used are observation, interviews, and documentation. The stages of data analysis are planning, acting, seeing, and reflecting. Based on the results of research that has been carried out using the think pair share type cooperative learning model on the theme of clean air for health in grade V of SD Negeri 101948 Bingkat, it shows that student learning activities have reached 93% in the Very Good category. The student's ability to solve pre-test questions has been completed. Based on the calculation of student learning outcomes, there were 3 students who got very high scores, 23 students who got high scores, 3 students who got enough scores, and 2 students who got low scores. Of the 31 students, 29 students have completed their studies.